IMPLEMENTASI PENDIDIKAN AGAMA DALAM PEMBENTUKAN KARAKTER ANAK USIA DINI DITADIKA AL FIQH ORCHARD - Dahlan, Alwi; Munawir Pasaribu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This qualitative descriptive study aims to analyze the implementation of Islamic Religious Education (PAI) in shaping the character of early childhood at Tadika Al-Fiqh Orchard Taman Setia, Malaysia. Data were collected through observation, in-depth interviews with teachers and parents, and documentation analysis. The results show that the teacher's role as a role model (uswah hasanah) and facilitator of Islamic habituation is the key factor directly influencing children's behavior. Parental support, manifested in trust in the institution, communication with teachers, and religious habituation at home, contributes significantly despite time limitations due to work commitments. The study also confirms that the quality of parental attention positively influences children's character development; children who receive adequate attention tend to exhibit more positive attitudes and behavior. Holistically, the synergy between teacher modeling at school and parental support at home albeit in different forms and intensities creates a consistent environment for instilling Islamic character. This research underscores the importance of integrated collaboration between educational institutions and families in effective character building through PAI.